Reduction of iron ore/empty fruit bunch char briquette composite - Yunus, Nurul Azhani; Ani, Mohd Hanafi; Mohd. Salleh, Hamzah; Jusoh @ Abd Rashid, Rusila Zamani; Akiyama, Tomohiro; Purwanto, Hadi (The Iron and Steel Institute of Japan, 2013)
Utilization of Malaysian low grade iron ore is an attractive option of domestic iron resource; however, extra energy consumption is required and thus contributes to greenhouse gases. In this study, incorporation of low grade iron ore deposits with oil palm waste as substitution of coke was studied. Briquette composites of iron ore and char derived from oil palm empty fruit bunch (EFB) pyrolysis were produced with minute amount of distilled water. Reduction processes were carried out at 873 K to 1 173 K under argon atmosphere in an electric furnace for briquette composites with different mass ratio of ore/char. For kinetic analysis, briquette with 8:2 ore/char ratio was used and reduction was carried out by varying the residence time. The percentage of reduction was estimated by oxygen removal and considering the weight loss. The structural and chemical changes of raw materials and briquettes were characterized using XRD, TG/DTA, and XRF. The results indicate that increasing in temperature, time and EFB char content in the briquette will increase the percentage of reduction. XRD and XRF results show that the original iron oxide hydrate has been transformed into partial wustite by several stages and the iron content increased up to 62.7 wt% for 6:4 ore/char ratio briquette. Kinetic results suggest that reduction of iron is controlled by gasification of carbon and the activation energy is 43.21 kJ. EFB char appears to be a promising energy source for replacing part of coal consumption in iron making, and reducing CO2 emission.